(untitled) (GnosisWisdom, 2023)
The objective of this article is to determine the influence of digital marketing on social networks for brand positioning for the company Fima Fabricante Industrial E.I.R.L. The methodology used is a quantitative approach, the type of research is applied, the level of research is applied - explanatory, the method used is experimental, the design is quasi-experimental. A questionnaire consisting of 20 questions with the Likert scale was applied. The population studied was made up of 25 potential clients. The findings were given by applying the Spearman correlation statistic, obtaining a result of (rho = 0.399), indicating that there is a positive influence of digital marketing on the brand positioning of Fima Fabricante Industrial E.I.R.L. It is concluded that digital Marketing has helped the company Fima Fabricante Industrial E.I.R.L to get closer to its customers, thus generating added value and therefore positioning the brand in the minds of its consumers.